2013
DOI: 10.1159/000353529
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Bleeding from Clean-Shave Haircuts: Detection with Blood Specific RNA Markers

Abstract: Background: ‘Haircut-associated bleeding' is a newly recognized entity that affects at least a quarter of African men who wear shiny clean-shave (‘chiskop') haircuts. Aim: This pilot study aimed to elucidate whether invisible haircut-associated bleeding was detectable using blood specific RNA markers (16 participants, 5 with unknown HIV status) and whether surface virus could be detected using PCR from scalp swabs (of 11 known HIV-positive participants). Methods: Haircuts were performed professionally and scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…[5,6] Invisible bleeding was recently detected from scalp swabs after professional clean-shave haircuts (with no visible injury on the scalp when examined by a dermatologist) in 37% of participants using genetic testing for bloodspecific RNA markers (albumin and haemoglobin beta (HBB)). [7] The potential transmission of blood-borne viruses such as hepatitis B (HBV) and HIV is most concerning. A study in Ethiopia reported that sharing shaving equipment in barber shops is common practice, [8] and an accidental scratch by sharp equipment in barber shops may create an opportunity for HIV and other blood-borne pathogens to enter the body.…”
Section: Researchmentioning
confidence: 99%
“…[5,6] Invisible bleeding was recently detected from scalp swabs after professional clean-shave haircuts (with no visible injury on the scalp when examined by a dermatologist) in 37% of participants using genetic testing for bloodspecific RNA markers (albumin and haemoglobin beta (HBB)). [7] The potential transmission of blood-borne viruses such as hepatitis B (HBV) and HIV is most concerning. A study in Ethiopia reported that sharing shaving equipment in barber shops is common practice, [8] and an accidental scratch by sharp equipment in barber shops may create an opportunity for HIV and other blood-borne pathogens to enter the body.…”
Section: Researchmentioning
confidence: 99%
“…To offset the psychological price of relinquishing amenities of using barbershop services (e.g., practical convenience or/and feeling well-groomed), social marketers should encourage purchasing and taking personal shaving kits to barbers. Research has suggested that the practice of using private shaving kits seems to coincide with lower HIV prevalence (3.6%) in Nigeria, a country that is three times more populous than South Africa but whose HIV prevalence is 17.8% (Arulogun & Adesoro, 2009; Khumalo, Gantsho, Gumedze, Mthebe, 2013; Salami et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As stipulated by the fundamental assumptions of the IMB model, successful promotion of hygienic hair care is predicated on whether relevant players (i.e., barbershop users, policy makers) are sufficiently motivated. Beliefs underlying the construct of relational motivation suggest that public health risks associated with barbershop use are ambivalently acknowledged as people seem torn between health risks observable in barbershops (see Arulogun & Adesoro, 2009; Khumalo, et al, 2013; Ngoboka, 2015) and the motivation to protect social relationships (Anangwe, 2009; Hornik, 2002; Pillaud et al, 2013). For such situations, Hornik (2002) outlines mechanisms through which exposure (through multiple communication channels) can foster publicity, social support and relevant partnerships (e.g., media and policy makers).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations